2019
DOI: 10.1371/journal.pone.0221931
|View full text |Cite
|
Sign up to set email alerts
|

Design of modular gellan gum hydrogel functionalized with avidin and biotinylated adhesive ligands for cell culture applications

Abstract: This article proposes the coupling of the recombinant protein avidin to the polysaccharide gellan gum to create a modular hydrogel substrate for 3D cell culture and tissue engineering. Avidin is capable of binding biotin, and thus biotinylated compounds can be tethered to the polymer network to improve cell response. The avidin is successfully conjugated to gellan gum and remains functional as shown with fluorescence titration and electrophoresis (SDS-PAGE). Self-standing hydrogels were formed using bioamines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Despite its interesting properties, unmodified Ge is a relatively bioinert material, showing a weak ability to support cell adhesion that limits its applications to anchorage‐independent cells 39,50 . To address this restriction and make it an optimal substitute for ECM for anchorage‐dependent cells, Ge must be modified 51,52 . Recently, Ge derivatization with RGD‐containing peptides has emerged as a highly effective strategy to enhance cell‐biomaterial interactions, by exploiting the affinity of integrins for the arginine‐glycine‐aspartic acid sequence 53–55 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite its interesting properties, unmodified Ge is a relatively bioinert material, showing a weak ability to support cell adhesion that limits its applications to anchorage‐independent cells 39,50 . To address this restriction and make it an optimal substitute for ECM for anchorage‐dependent cells, Ge must be modified 51,52 . Recently, Ge derivatization with RGD‐containing peptides has emerged as a highly effective strategy to enhance cell‐biomaterial interactions, by exploiting the affinity of integrins for the arginine‐glycine‐aspartic acid sequence 53–55 .…”
Section: Resultsmentioning
confidence: 99%
“…39,50 To address this restriction and make it an optimal substitute for ECM for anchorage-dependent cells, Ge must be modified. 51,52 Recently, Ge derivatization with RGD-containing peptides has emerged as a highly effective strategy to enhance cellbiomaterial interactions, by exploiting the affinity of integrins for the arginine-glycine-aspartic acid sequence. [53][54][55] In this work, a dextran methacylate (DexMa)/gellan-RGD (GeRGD)-based IPN system was developed using glycerol as a non-conventional solvent, which allows both to speed up the kinetic of crosslinking, thanks to its capability to act as a co-initiator in the radical process 32 and to provide the polymeric mixture with enhanced viscoelastic properties that make it suitable as bioink to print different complex scaffolds.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…36 Also, avidinconjugated gellan gum hydrogel has been prepared and functionalized by biotinylated adhesive ligands such as B-FN and biotinylated cyclic RGD; this was demonstrated to be a promising tool for 3D cell culture studies. 37 Recently, Fernandes et al used avidin and biotinylated multi-arm PEGs to design affinity-triggered hydrogels. The authors showed that avidin and PEG-[biotin] 4 were capable to selfassemble instantaneously, and these hydrogels were used to encapsulate pluripotent stem cells and to induce neural lineage.…”
Section: Introductionmentioning
confidence: 99%
“…Avidin retained its biotin-binding activity during the 3D printing process . Also, avidin-conjugated gellan gum hydrogel has been prepared and functionalized by biotinylated adhesive ligands such as B-FN and biotinylated cyclic RGD; this was demonstrated to be a promising tool for 3D cell culture studies . Recently, Fernandes et al used avidin and biotinylated multi-arm PEGs to design affinity-triggered hydrogels.…”
Section: Introductionmentioning
confidence: 99%